2016
DOI: 10.20960/nh.309
|View full text |Cite
|
Sign up to set email alerts
|

Impact of physical activity and sedentarism on hydration status and liquid intake in Spanish older adults. The PHYSMED study

Abstract: Introduction: Data on hydration status in older adults are scarce and there are very few studies focusing on the impact of physical activity (PA) on drinking behavior. Objective: To assess the impact of physical activity and sedentarism on fl uid intake in Spanish elderly. Methods: 433 non-institutionalized Spanish older adults (58% females), aged 55-88 years, volunteered for the PHYSMED study. PA data were obtained by means of the Minnesota and EXERNET questionnaires. Population was divided into four groups: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
2
8
0
1
Order By: Relevance
“…As far as we know, the effects of compliance with the PA guidelines on the state of hydration in schoolchildren have not been evaluated. Similar data have been found in the PHYSMED study [61] conducted in a Spanish adult population aged 55 to 88 years old in which, similar to the results obtained in the present study, significant differences were observed in the plasma osmolality between the "sedentary inactive" and "non-sedentary active" groups.…”
Section: Discussionsupporting
confidence: 92%
“…As far as we know, the effects of compliance with the PA guidelines on the state of hydration in schoolchildren have not been evaluated. Similar data have been found in the PHYSMED study [61] conducted in a Spanish adult population aged 55 to 88 years old in which, similar to the results obtained in the present study, significant differences were observed in the plasma osmolality between the "sedentary inactive" and "non-sedentary active" groups.…”
Section: Discussionsupporting
confidence: 92%
“…The study confirmed on the sample of 6508 participants aged > 18 years that the greater the physical activity, the greater the beverages consumption. Finally, the same pattern was found in a Spanish study involving 433 non-institutionalized older adults aged 55-88 years (Aparicio-Ugarriza et al, 2016). It is therefore probable that people with regular PA have an overall healthier lifestyle, including better fluid replenishment.…”
Section: Discussionsupporting
confidence: 73%
“…Nutrient adequacy and food patterns have been linked to PA, with a higher percent of subjects meeting DRIs with increased PA level [ 39 ]. In a study performed in elderly Spanish subjects, higher amounts of water and other beverages were consumed by those being active and low sedentary than in the other PA groups [ 40 ]. Positive metabolic effects of regular PA are explicitly demonstrated in the scientific literature [ 41 ].…”
Section: Discussionmentioning
confidence: 99%